\(=\dfrac{2x+4+3x-6-18+5x}{\left(x-2\right)\left(x+2\right)}=\dfrac{10x-20}{\left(x-2\right)\left(x+2\right)}=\dfrac{10}{x+2}\)
Đúng 1
Bình luận (0)
\(=\dfrac{2x+4+3x-6-18+5x}{\left(x-2\right)\left(x+2\right)}=\dfrac{10x-20}{\left(x-2\right)\left(x+2\right)}=\dfrac{10}{x+2}\)
Thực hiện phép tính :
Thực hiện phép tính :
3 6 - x
_____ + ________
2x+6 2x^2 + 6x
Thực hiện phép tính
Thực hiện phép tính:
Thực hiện phép tính
Thực hiện phép tính
Thực hiện phép tính
Thực hiện phép tính
Thực hiện phép tính :
thực hiện phép tính
Thực hiện phép tính